Butyrate Protects Mice Against Methionine–Choline-Deficient Diet-Induced Non-alcoholic Steatohepatitis by Improving Gut Barrier Function, Attenuating Inflammation and Reducing Endotoxin Levels - Ye, Jianzhong; Lv, Longxian; Wu, Wenrui; Li, Yating; Shi, Ding; Fang, Daiqiong; Guo, Feifei; Jiang, Huiyong; Yan, Ren; Ye, Wanchun; Li, Lanjuan (Frontiers in Microbiology, 2018)
Butyrate exerts protective effects against non-alcoholic steatohepatitis (NASH), but the underlying mechanisms are unclear. We aimed to investigate the role of butyrate-induced gut microbiota and metabolism in NASH development. Sixty-five C57BL/6J mice were divided into four groups (n = 15–17 per group) and were fed either a methionine–choline-sufficient (MCS) diet or methionine–choline-deficient (MCD) diet with or without sodium butyrate (SoB; 0.6 g/kg body weight) supplementation for 6 weeks. Liver injury, systematic inflammation, and gut barrier function were determined. Fecal microbiome and metabolome were analyzed using 16S rRNA deep sequencing and gas chromatography-mass spectrometry (GC-MS). The results showed that butyrate alleviated the MCD diet-induced microbiome dysbiosis, as evidenced by a significantly clustered configuration separate from that of the MCD group and by the depletion of Bilophila and Rikenellaceae and enrichment of promising probiotic genera Akkermansia, Roseburia, Coprococcus, Coprobacillus, Delftia, Sutterella, and Coriobacteriaceae genera. The fecal metabolomic profile was also substantially improved by butyrate; several butyrate-responsive metabolites involved in lipid metabolism and other pathways, such as stearic acid, behenic acid, oleic acid, linoleic acid, squalene, and arachidonic acid, were identified. Correlation analysis of the interaction matrix indicated that the modified gut microbiota and fecal metabolites induced by butyrate were strongly correlated with the alleviation of hepatic injury, fibrosis progression, inflammation, and lipid metabolism and intestinal barrier dysfunction. In conclusion, our results demonstrated that butyrate exerts protective effects against NASH development, and these effects may be driven by the protective gut microbiome and metabolome induced by butyrate. This study thus provides new insights into NASH prevention.